Pengaruh Limbah Beton Mutu Tinggi Sebagai Alternatif Campuran Agregat Kasar Terhadap Kuat Tekan Beton Nama Penulis - Teguh Santoso; Januar Sasongko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the use of high-strength concrete waste (HSCW) as a coarse aggregate replacement and its effect on the compressive strength of concrete with a target strength of 32 MPa. Cylindrical specimens measuring 15 cm in diameter and 30 cm in height were used. HSCW was used in varying proportions: 25%, 50%, 75%, and 100%, with conventional concrete as the control. Each variation included nine specimens. The research employed an experimental approach. Results show that HSCW affects compressive strength. The control concrete reached 39.63 MPa. At 25% HSCW, strength increased to 40.73 MPa (2.78% gain), but declined at higher levels: 50% (40.19 MPa), 75% (36.66 MPa), and 100% (35.63 MPa), indicating a significant reduction at higher replacement rates.